An Overview of α-Pyrones as Phytotoxins Produced by Plant Pathogen Fungi - Antonio Evidente (Molecules, 2025)
Crop diseases negatively affect the quality and quantity of agricultural products, with significant economic and social consequences. These problems become emergencies in a world where the safe production of food for human health is becoming increasingly pressing. Microorganisms, including phytopathogenic fungi, are the main organisms responsible for these diseases, which cause devastating damage. Environmental pollution generated by human activities causes further significant reductions in agricultural production, as well as the expansion of metropolitan areas, and climate change. Phytotoxins produced by pathogenic fungi play a fundamental role in the induction of diseases by directly interfering with the physiological processes of agricultural plants. They are secondary metabolites that can belong to all the different classes of natural compounds, and their structures and biological activities have been extensively studied. These substances have often been shown to possess other interesting biological activities for potential applications both in agriculture and in other fields, such as biotechnology and medicine. This review focuses on phytotoxic α-pyrones produced by plant pathogenic fungi, describing in detail all their chemical and biological properties and, in some cases, the results of studies on their structure-activity relationship and on the potential practical applications in various sectors.